Citotoxicidade de alguns cimentos reparadores de perfuração radicular sobre células L929 - Miranda, Rosana Belchior (2007)
Mineral trioxide aggregate has been widely used to repair root perforations because of its excellent physical, chemical and biological properties, showed through research and clinical results. The white MTA has become available for the aesthetic needs. A new experimental epoxy resin and calcium hidroxide based cement (MBPc) is being developed to the same purpose of MTA. The aim of the present study was to compare the cytotoxicity of the experimental MBPc and the MTA Branco Angelus® with gray ProRoot™ MTA, that is worldwide known as biocompatible. The agar overlay method with neutral red dye was used onto L929 cells. Cells were seeded into 6-well culture plates at an inicial density of 2 X 105 cells/ ml in Dulbecco’s MEM with 5% bovine fetal serum. Three samples of each 48-h set test materials, teflon as negative control and latex as positive control were placed on the agar overlay. After an incubation period of 24 h at 37º C in a humidified atmosphere of 5% CO2 in air, the nonviable cells area was measured. The average values were turn into grades in accord to POP/FIOCRUZ table. The zones of lysis and the cell morphology were examined in a inverted microscope. The results showed grade 1 (slight) for the two types of MTA (p > 0,05) and grade 2 (mild) for the MBPc (p < 0,001). All the samples met the requirements of the test because none of the cultures exposed to the test cements showed reactivity higher than grade 2.